A conceptual study on Islamic corporate governance model in curtailing bank’s fraud - Yusuf, Ali Danladi; Ahmad, Umar; Ahmad Razimi, Mohd Shahril (Science Publications, 2016)
The paper intends to discuss the concepts, framework, structure of fraud, and its two contending theories i.e. Fraud Triangle Theory and Fraud Diamond Theory. The paper also intends to analyse the concept of Islamic corporate governance, its theories and the popular theory of Shariah Enterprise Theory (S.E.T), which if properly implemented and giving a sound attention, the issue of fraud in Islamic banks will be a thing of the past.After the extend literature review this paper proposed model as re-examined by some scholars, to see whether the model is viable in today’s multi-faith, and multi-cultural society of 21th century and the likely challenges it might face.